REFORMULASI PENAFSIRAN RUH MENURUT ZEZEN ZAINAL ABIDIN BAZUL ASYHAB - Yasser Muda Lubis; Salman AlFarizi (Universitas PTIQ Jakarta, 2022)
The purpose of this study is to find out and understand the meaning of the spirit in general in the Qur'an and specifically according to Zezen's Thoughts Zainal Abidin Bazul Asyhab. He is one of the Archipelago Figures, Charismatic Ulama from West Java and he is one of the Sufi figures whose thoughts in his study, especially on the study of interpretation, are considered productive and have significant and substantive contributions. The researcher describes Zezen's findings that reveal the meaning of spirit in the Qur'an by taking verses from the Qur'an, namely QS: al-Isra' verse 85 which is the basis of the polemic of the discussion about the spirit whose findings are that the discussion about the spirit is very broad. and not only half understood. The findings of the discussion of the spirit in the Qur'an are very broad and there are various meanings of the pronunciation of the spirit in the Qur'an and its relation is very important for humans to know and understand the divinity dimension that exists within themselves, especially as God's perfect creation.